Final answer:
The equation in factored form given the zeros -2 and 2 with the vertex (0,-4) is f(x) = -(x + 2)(x - 2).
Step-by-step explanation:
To find the equation in factored form given the zeros = -2 and 2 with the vertex (0,-4), we start with the standard form of a quadratic function, which is f(x) = ax^2 + bx + c. Since the vertex is at the origin and the parabola opens upward (the coefficient of x^2 is positive), and the factor form of the quadratic equation is f(x) = a(x - p)(x - q), where p and q are the zeros of the function.
In this case, using the given zeros of -2 and 2, the factored form starts as f(x) = a(x + 2)(x - 2). To find the value of a, we use the vertex (0,-4). The vertex form of a quadratic function is f(x) = a(x - h)^2 + k, where the vertex is at the point (h,k). Comparing the vertex form with the vertex given, we get f(x) = a(x - 0)^2 - 4. Since when x = 0, f(x) = -4, we can see that a must be -1. Therefore, the factored form of the quadratic function is f(x) = -1(x + 2)(x - 2) or f(x) = -(x + 2)(x - 2).